1983
DOI: 10.1128/aem.45.6.1775-1779.1983
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mineral Uptake by Zea mays and Sorghum bicolor Roots Inoculated with Azospirillum brasilense

Abstract: Inoculation of corn (Zea mays) seeds with Azospirillum brasilense strain Cd or Sp 7 significantly enhanced (30 to 50% over controls) the uptake of N03 , K+, and H2PO4 into 3-to 4-dayand 2-week-old root segments. No gross changes in root morphology were observed; altered cell arrangement in the outer four or five layers of the cortex was seen in photomicrographs of cross sections of inoculated corn roots. The surface activity involved in ion uptake probably increased, as shown by the darker staining by methylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
7

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(68 citation statements)
references
References 12 publications
5
56
0
7
Order By: Relevance
“…Biomass yield increased under application of biofertilizers, because there was a significant increase in the dry weight of shoots at the prestilking stage, that may be related to the favouritism of some environmental factors which directly affected the bio fertilizer and its impact on the nutrient availability and growth, which positively influenced maize photosynthesis and dry matter accumulation more actively that agree with [15,16]. Azimi et al [17] found that application of Supernitroplus biofertilizer with Phosphate (Barvar 2) treatment had the highest seed yield (7.6 ton/ha) and non-application of biofertilizers treatment that had Pishtaz cultivar had the lowest seed yield (6.3 ton/ha) [18]. Also, Azimi et al [18] found that the application nitrogen and phosphate biofertilizers increased yield and yield components of barley under Boroujerd environmental condition.…”
Section: Yield Componentssupporting
confidence: 80%
“…Biomass yield increased under application of biofertilizers, because there was a significant increase in the dry weight of shoots at the prestilking stage, that may be related to the favouritism of some environmental factors which directly affected the bio fertilizer and its impact on the nutrient availability and growth, which positively influenced maize photosynthesis and dry matter accumulation more actively that agree with [15,16]. Azimi et al [17] found that application of Supernitroplus biofertilizer with Phosphate (Barvar 2) treatment had the highest seed yield (7.6 ton/ha) and non-application of biofertilizers treatment that had Pishtaz cultivar had the lowest seed yield (6.3 ton/ha) [18]. Also, Azimi et al [18] found that the application nitrogen and phosphate biofertilizers increased yield and yield components of barley under Boroujerd environmental condition.…”
Section: Yield Componentssupporting
confidence: 80%
“…Grain yield increase was reported with the bio fertilizer applications which account important benefit to the maize producers and maize production, causing decreasing in the inputs of production because of economizing much money to chemical fertilizers and increasing in grain yield (Azimi et al2013). It is impact on the nutrient availability and growth, which positively influenced the maize photosynthesis and dry matter accumulation more actively that agree with Lin et al 1983, Shevananda, 2008and Beyranvand 2013…”
Section: Grain Yield and 1000 Grain-weightsupporting
confidence: 73%
“…Based on these findings, lumichrome could be viewed as a previously unrecognized signal molecule (Dakora et al, 2001), and if so, then it has to be transported from roots to shoots where it effects the observed developmental changes. Some plant signals such as ABA are similarly transported from root to shoot in the xylem stream (Lin et al, 1983;Chen et al, 2002;Maurel et al, 2004). Apart from establishing the presence of lumichrome in xylem (Fig.…”
Section: Xylem Transport and In Situ Accumulation In Leaves: A Putatimentioning
confidence: 99%